A Randomized Clinical Trial of Transgender Women Switching to B/F/TAF: The (mo)BETTA Trial. (5th April 2023) - Lake, Jordan E; Hyatt, Ana N; Feng, Han; Debroy, Paula; Kettelhut, Aaren; Miao, Hongyu; Peng, Liming; Bhasin, Shalender; Bell, Susan; Rianon, Nahid; Brown, Todd T; Funderburg, Nicholas T
Abstract: Background: Cardiometabolic disease in transgender women (TW) is affected by gender-affirming hormonal therapies (GAHTs), HIV, and antiretroviral therapy (ART). We evaluated the 48-week safety/tolerability of switching to bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) vs continued ART in TW on GAHT. Methods: TW on GAHT and suppressive ART were randomized 1:1 to switch to B/F/TAF (Arm A) or continue current ART (Arm B). Cardiometabolic biomarkers, sex hormones, bone mineral density (BMD) and lean/fat mass by DXA scan, and hepatic fat (controlled continuation parameter [CAP]) were measured. Wilcoxon rank-sum/signed-rank and χ 2 tests compared continuous and categorical variables. Results: TW (Arm A n = 12, Arm B n = 9) had a median age of 45 years. Ninety-five percent were non-White; 70% were on elvitegravir or dolutegravir, 57% TAF, 24% abacavir, and 19% TDF; 29% had hypertension, 5% diabetes, and 62% dyslipidemia. There were no adverse events. Arm A/B had 91%/89% undetectable HIV-1 RNA at week 48 (w48). Baseline (BL) osteopenia (Arm A/B 42%/25%) and osteoporosis (17%/13%) were common, without significant changes. BL lean/fat mass were similar. At w48, Arm A had stable lean mass but increased limb (3 lbs) and trunk (3 lbs) fat (within-arm P < .05); fat in Arm B remained stable. No changes occurred in lipid or glucose profiles. Arm B had a greater w48 decrease (−25 vs −3 dB/m; P = .03) in CAP. BL and w48 concentrations of all biomarkers were similar. Conclusions: In this cohort of TW, switch to B/F/TAF was safe and metabolically neutral, though greater fat gain occurred on B/F/TAF. Further study is needed to better understand cardiometabolic disease burden in TW with HIV.